Knowledge, attitude and practices of childhood diarrhoea among mothers of children under five years of age: a cross sectional study - Garg, Nitish; Kikon, Sulanthung; Ramesh, Rohan Michael; Garg, Sugandha Chaudhary (International Journal Of Community Medicine And Public Health, 2019)
Background: Diarrhoea is an important communicable disease which can be prevented by proper hygiene and other simple practical measures. We assessed the knowledge, attitude and practices among mothers regarding childhood diarrhoea in a secondary care hospital in Dimapur, Nagaland. Methods: Cross-sectional observational study conducted over a period of one year including 449 mothers in the age group <45 years with atleast one child under 5 years of age using an interviewer administered, pilot tested, semi-structured questionnaire under the following as categories demography, knowledge, attitude and practices. Results: 97.8% had good knowledge regarding causes and prevention of diarrhoea, 65% had good knowledge regarding the management of diarrhoea while 31% mothers had moderate knowledge. 98% mothers had good attitude but only 17.8% had good practice scores. Multivariate regression analysis showed education > class 10 and residence in urban area were significantly associated with good knowledge and education >class 10, age of mothers ≥29 years, employed mothers, family income Rs. ≥28000 were significantly associated with good practice. Conclusions: Good knowledge and attitude regarding diarrhoea prevention and management among our study population did not translate to good practice. These could also be due to the lower knowledge about management of diarrhoea. Widespread prevalence of wrong practices in the community like irrational use of antibiotics could also have resulted in low practice scores. The gaps between knowledge and attitude and practices among the mothers need to be addressed.